PENGUATAN SUMBER DAYA MANUSIA PADA LEMBAGA PENDIDIKAN ISLAM: Dari Problem Filosofis Menuju Manajemen Strategis - Majid, Mohammad Arif; Sudarto, Sudarto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2022)
Strengthening Human Resources (HR) is fundamental to the existence of every institution, whether it is public or private. Islamic education institutions as public services engaged in educational services absolutely have ideal human resources so that they are competitive. To have ideal and competitive human resources, it is necessary to make every effort to manage human resources effectively and professionally. This article aims to find out how to apply human resource management, the application of human resource management in improving the quality of educational services, and various philosophically fundamental issues that emphasize that the process of strengthening human resources needs to involve awareness, concern for institutions, as well as various ideological issues. which fosters a sense of mutual support and active participation of teachers/lecturers in the transfer of knowledge. Institutions should be able to provide solutions to existing obstacles by building shared awareness, equating vision and goals, building a sense of togetherness, making positive contributions, fostering an orientation towards development, and being able to build intense collaboration between guardians of students/students, institutions. And society. Keywords: strengthening human resources, islamic education